Early liver transplantation for severe alcohol-related hepatitis not responding to medical treatment: a prospective controlled study. (May 2022) - Louvet, Alexandre; Labreuche, Julien; Moreno, Christophe; Vanlemmens, Claire; Moirand, Romain; Féray, Cyrille; Dumortier, Jérôme; Pageaux, Georges-Philippe; Bureau, Christophe; Chermak, Faïza; Duvoux, Christophe; Thabut, Dominique; et al.
Summary: Background: Early liver transplantation for severe alcohol-related hepatitis is an emerging treatment option. We aimed to assess the risk of alcohol relapse 2 years after early liver transplantation for alcohol-related hepatitis compared with liver transplantation for alcohol-related cirrhosis after at least 6 months of abstinence. Methods: We conducted a multicentre, non-randomised, non-inferiority, controlled study in 19 French and Belgian hospitals. All participants were aged 18 years or older. There were three groups of patients recruited prospectively: patients with severe alcohol-related hepatitis who did not respond to medical treatment and were eligible for early liver transplantation according to a new selection scoring system based on social and addiction items that can be quantified in points (early transplantation group); patients with alcohol-related cirrhosis listed for liver transplantation after at least 6 months of abstinence (standard transplantation group); patients with severe alcohol-related hepatitis not responding to medical treatment not eligible for early liver transplantation according to the selection score (not eligible for early transplantation group), this group did not enter any further liver transplantation processes. We also defined a historical control group of patients with severe alcohol-related hepatitis unresponsive to medical therapy and non-transplanted. The primary outcome was the non-inferiority of 2-year rate of alcohol relapse after transplantation in the early transplantation group compared with the standard transplantation group using the alcohol timeline follow back (TLFB) method and a prespecified non-inferiority margin of 10%. Secondary outcomes were the pattern of alcohol relapse, 2-year survival rate post-transplant in the early transplantation group compared with the standard transplantation group, and 2-year overall survival in the early transplantation group compared with patients in the not eligible for early transplantation group and historical controls. This trial is registered with ClinicalTrials.gov, NCT01756794 . Findings: Between Dec 5, 2012, and June 30, 2016, we included 149 patients with severe alcohol-related hepatitis: 102 in the early transplantation group and 47 in the not eligible for early transplantation group. 129 patients were included in the standard transplantation group. 68 patients in the early transplantation group and 93 patients in the standard transplantation group received a liver transplant. 23 (34%) patients relapsed in the early transplantation group, and 23 (25%) patients relapsed in the standard transplantation group; therefore, the non-inferiority of early transplantation versus standard transplantation was not demonstrated (absolute difference 9·1% [95% CI –∞ to 21·1]; p=0·45). The 2-year rate of high alcohol intake was greater in the early transplantation group than the standard transplantation group (absolute difference 16·7% [95% CI 5·8–27·6]) The time spent drinking alcohol was not different between the two groups (standardised difference 0·24 [95% CI −0·07 to 0·55]), but the time spent drinking a large quantity of alcohol was higher in the early transplantation group than the standard transplantation group (standardised difference 0·50 [95% CI 0·17–0·82]). 2-year post-transplant survival was similar between the early transplantation group and the standard transplantation group (hazard ratio [HR] 0·87 [95% CI 0·33–2·26]); 2-year overall survival was higher in the early transplantation group than the not eligible for early transplantation group and historical controls (HR 0·27 [95% CI 0·16–0·47] and 0·21 [0·13–0·32]). Interpretation: We cannot conclude non-inferiority in terms of rate of alcohol relapse post-transplant between early liver transplantation and standard transplantation. High alcohol intake is more frequent after early liver transplantation. This prospective controlled study confirms the important survival benefit related to early liver transplantation for severe alcohol-related hepatitis; and this study provides objective data on survival and alcohol relapse to tailor the management of patients with severe alcohol-related hepatitis. Funding: The present study has been granted by the French Ministry of Health—Programme Hospitalier de Recherche Clinique 2010.